Mathematical Literacy of Junior High School Students in Solving Problems PISA Content Quantity - Nais Qonita Salsabila (Journal of Mathematics and Mathematics Education, 2024)
Mathematical literacy is defined as students’ capacity to formulate, employ and interpret mathematics in a variety of contexts. It includes reasoning mathematically and using mathematical concepts, procedures, facts and tools to describe, explain and predict phenomena. It assists individuals in recognising the role that mathematics plays in the world and to make the well-founded judgements and decisions needed by constructive, engaged and reflective citizens. Quantity content includes the ability in reasoning quantitatively, representing something into numbers, understanding mathematical steps, counting by heart and making assessments. The questions on quantity content are mostly implemented in everyday life, such as in exchanging currency exchange rates, determining bank interest, shopping, calculating taxes, measuring time, measuring distance and others. The purpose of this article is to describe the level of mathematical literacy ability of junior high school students in solving Quantity content PISA questions. The data from this study were taken from the results of the PISA test questions on quantity content and interviews. Subject taking is based on the test results of students who have the highest scores, as it is expected to get the results of the analysis of students’ high literacy skills. In this research, the researcher is using indicators of mathematical literacy level according to PISA. Based on the results of research and discussion, it is concluded that there are students who have high mathematical literacy skills equivalent to level 5.